2020
DOI: 10.1002/cyto.a.24047
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Fever, COVID‐19 (SARS‐CoV‐2), and Antibody‐Dependent Enhancement (ADE): A Perspective

Abstract: SARS-CoV-2 pandemic and recurrent dengue epidemics in tropical countries have turned into a global health threat. While both virus-caused infections may only reveal light symptoms, they can also cause severe diseases. Here, we review the possible antibody-dependent enhancement (ADE) occurrence, known for dengue infections, when there is a second infection with a different virus strain. Consequently, preexisting antibodies do not neutralize infection, but enhance it, possibly by triggering Fcγ receptor-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(64 citation statements)
references
References 61 publications
2
61
0
1
Order By: Relevance
“…Such a mechanism for SARS-CoV-2 is not yet fully understood, but previous coronavirus infections or SARS-CoV-2 convalescent patients with different SARS-CoV-2 strains could promote ADE, as experimentally shown for antibodies against the MERS-CoV or SARS-CoV-1 spike S protein (72). Several studies have shown that sera administration induced increased SARS-CoV-1 viral entry into cells that express the Fc receptor, and serum-dependent SARS-CoV-1 entry does not pass through the endosome pathway (73,74).…”
Section: Pathogenesis Of Sars-cov-2 Viral Entry and Replicationmentioning
confidence: 99%
“…Such a mechanism for SARS-CoV-2 is not yet fully understood, but previous coronavirus infections or SARS-CoV-2 convalescent patients with different SARS-CoV-2 strains could promote ADE, as experimentally shown for antibodies against the MERS-CoV or SARS-CoV-1 spike S protein (72). Several studies have shown that sera administration induced increased SARS-CoV-1 viral entry into cells that express the Fc receptor, and serum-dependent SARS-CoV-1 entry does not pass through the endosome pathway (73,74).…”
Section: Pathogenesis Of Sars-cov-2 Viral Entry and Replicationmentioning
confidence: 99%
“…The invention of a successful and widely available COVID-19 vaccine will be a great leap forward for humankind, but there are several challenges to overcome: (1) a lack of understanding of the pathogenesis and the predictive role of vaccines in the clinical pathway of persons being infected by SARS-CoV-2 [5][6][7], (2) a huge disagreement among experts about how to determine the most immunogenic epitopes and antigens of SARS-CoV-2 [8,9], (3) the finding that antibody-dependent enhancement (ADE) may contribute to the exaggeration of SARS-CoV-2 disease [10,11], (4) the lack of established animal models for COVID-19 vaccine challenge testing, which raises the speculation of using controlled human infection (CHI) as a potential approach [3], and finally, (5) speculation that the duration of protection by immune response in natural infection is not long enough [12].…”
Section: Introductionmentioning
confidence: 99%
“…Such antibodies would bind, but not neutralize, and would eventually enhance disease severity, possibly by triggering Fcγ receptor-mediated uptake of virus by myeloid cells and subsequent cytokine storm 13 . While data in support of such mechanisms in COVID-19 are missing 14 , conflicting experimental data have been presented for antibodies to the S proteins of the coronaviruses MERS-CoV or SARS-CoV 15 . In this context, Jeff Ravetch (Rockefeller University) highlighted the importance of interactions between the immunoglobulin Fc fragment and its receptor FcR in modulating innate and adaptive immune responses to viruses.…”
Section: B Cell Immunitymentioning
confidence: 99%